Global Economic Risks and the Problem of Economic Security of the State - Semenova Kateryna D.; Tarasova Krystyna I. (Bìznes Inform, 2019)
The article is aimed at analyzing the problem of global risks of modern era. Using the data obtained by experts from the World Economic Forum for 2017-2019, the authors found the five most dangerous global risks in terms of both the likelihood of an occurrence and the scale of the impact. The research identifies tendencies in changing global risks over recent years. It is specified that the main risks are found in the sphere of environment, ecology and technological security (cyber-risks). The emphasis is placed on researching global economic risks. The main factors of global economic risk are: the trade war between the United States and China; the large burden of the U.S. corporate debt; the crisis status of the markets in developing countries; China’s weak macroeconomic policy; cyberwarfare, as well as Italy’s political and financial instability. Prospects for further research in this direction is an analysis of geopolitical and technological risks, which increase economic risks, as well as prediction of the probability of a particular economic risk in both short- and medium-term.